Intrathecal administration of botulinum toxin type A improves urinary bladder function and reduces pain in rats with cystitis. (23rd April 2014) - Coelho, A.; Oliveira, R.; Rossetto, O.; Cruz, C.D.; Cruz, F.; Avelino, A.
Abstract Background Botulinum toxin A (Onabot/A) has been shown to have an antinociceptive effect. This might be due to an impairment of sensory nerves not only in the peripheral but also in the central nervous system. In this work, we analysed both systems by studying the effect of intrathecal (i.t.) administration of botulinum toxin A in an animal model of bladder pain and hyperactivity induced by cyclophosphamide (CYP). Methods Rats were implanted with an i.t. catheter at the L6 segment. Bladder pain was induced by intraperitoneal (i.p.) injection of CYP. Five experimental groups were created: (1) Saline i.p. + i.t.; (2) Onabot/A i.t.; (3) CYP i.p. + saline i.t.; (4) CYP i.p. + Onabot/A i.t. 48 h after CYP; and (5) Onabot/A i.t. 30 days. Mechanical sensitivity was assessed in the abdomen and hindpaws. Motor activity was observed in an open‐field arena. Bladder reflex activity was evaluated by cystometry. At the end, bladders and spinal cord were immunoreacted (IR) against cleaved SNAP‐25 (cSNAP‐25), c‐Fos, p‐ERK, calcitonin gene‐related peptide (CGRP) and GAP43. Results The toxin reduced pain symptoms, bladder hyperactivity, expression of neuronal activation markers and CGRP, typically up‐regulated in this inflammatory model. The presence of cSNAP‐25 was detected in the spinal cord and bladder fibres from animals treated with Onabot/A. No somatic or visceral motor impairments were observed. Conclusions Our findings suggest that i.t. Onabot/A has a strong analgesic effect in a model of severe bladder pain. This route of administration can be further explored to treat intractable forms of pain.